SISTEM INFORMASI ABSENSI PEGAWAI HONORER BERBASIS WEB PADA UPTD PELAYANAN INFRASTRUKTUR IRIGASI WILAYAH III CIRANJANG - Hanidah, Isti Ayu; Kurniawati, Laela (Bianglala Informatika, 2025)
UPTD Pelayanan Infrastruktur Irigasi Wilayah III Ciranjang is a technical implementing element of the Public Works and Spatial Planning Agency of Cianjur Regency which carries out technical operational activities in the field of Water Resources Operation and Maintenance. The attendance system for honorary employees is still manual so that it is prone to errors in the attendance system. The attendance system is very important in a company or agency to determine the presence of employees in a company or agency, this is related to discipline and has an impact on the performance of each employee. Therefore, in implementing the attendance process, accuracy is needed so as not to hinder the performance of the company or agency. The design of web-based employee attendance at Pelayanan Infrastruktur Irigasi Wilayah III Ciranjang to simplify and accelerate the attendance process and monitor employee attendance efficiently and effectively. This application is designed with a waterfall model, this application is built with the PHP programming language and MySQL as a data storage medium. Keywords: Manual, Attendance System, Website